Acute effect of a foam roller on the mechanical properties of the rectus femoris based on tensiomyography in soccer players (International Journal of Human Movement and Sports Sciences, 2016)
Tensiomyography (TMG) is a relatively new technique to assess the muscles mechanical properties in response to a single electrical stimulus. The purpose of the present study was to assess the acute effect of a foam roller (FR) in the rectus femoris muscle using TMG. Seventeen male professional soccer players (age 21.4 ± 3.8 years, height 180.5 ± 7.7 cm, and mass 73.6 ± 10.7 kg) performed 4 sets of with a duration of 15s using the foam roller (FR) on the dominant leg with 2 min of rest at 30 beats per minute. TMG measurements were performed at rest after the second and fourth sets for both the dominant and non-dominant leg (control). The TMG parameters analysed included stiffness (Dm), and contraction time (Tc). Substantial differences were not found between the legs at rest. For the non-dominant leg, substantial differences in Dm were found after the second and the fourth sets. For the dominant leg, substantial differences in Dm were not observed after the FR was applied. No differences in Tc were found for any of the measurements. Our results suggest that the use of a foam roller in slowly executed small sets maintains the muscle stiffness and the contraction time of the RF.